PERLINDUNGAN HUKUM BAGI BIDAN DALAM PEMBERIAN PELAYANAN UMUM DI KLINIK PRAKTIK MANDIRI BIDAN - Rifaat Hanifa Muslimah (2022)
A midwife is a woman who has completed a midwifery education program that is legally recognized by the central government and has fulfilled the requirements to practice midwifery. Midwives as health workers in carrying out their duties have the right to obtain legal protection, occupational safety, and health treatment following human dignity as long as they carry out their duties under professional standards, service standards, and standard operating procedures. The research objectives were to determine the legal protection for midwives at the Independent Midwifery Practice Clinics in providing public services if there were no other health care facilities or at the request of the patient and to determine the midwives' authority at the Independent Midwifery Practice Clinics in providing public services in terms of the Law of Republic of Indonesia No. 4 of 2019 concerning Midwifery. The research design was qualitative research with an empirical normative approach. The data obtained were studied and discussed as a comprehensive material that produced analytical descriptive data. The research results showed that legal protection for midwives in providing health services in Independent Midwifery Practice Clinics was a right granted by law as long as the midwife performed her duties under professional standards, standard operating procedures, and authorities as regulated in Law of the Republic of Indonesia No. 4 of 2019 concerning Midwifery, Law Number 36 of 2009 concerning Health, Law Number 36 of 2014 concerning Health Workers, and Regulation of the Minister of Health of the Republic of Indonesia Number 28 of 2017 concerning Permits and Implementation of Midwifery Practices. The legal protection was given to midwives who have delegated authority from doctors in hospitals. It was regulated in Article 46 of the Law of the Republic of Indonesia Number 44 of 2009 concerning Hospitals. However, midwives who have delegated authority from doctors at the primary health care were still required to be reviewed because the rules regarding primary health care did not contain provisions for the legal responsibility of Primary Health Care for the negligence of medical personnel and health workers. Furthermore, it was still not clear and detailed what medical actions could be taken in delegating authority to midwives. This research suggested that midwives must be aware that every action or service provided to patients is legally binding. Therefore, midwives must know the limits of their authority according to competence to avoid mistakes, negligence, or acts against the law. Keywords: Legal Protection, Midwife, Service Delivery, Independent Midwifery Practice Clinics.